The Precision Analysis of Cutting Edge Preparation on CBN Cutting Inserts Using Rotary Ultrasonic Machining - Marcel Kuruc; Tomáš Vopát; Jana Moravčíková; Ján Milde (Micromachines, 2022)
This paper is focused on the issue of preparing the cutting edge microgeometry of cutting inserts made of cubic boron nitride (CBN). The aim of this research was to investigate the possibilities of rotary ultrasonic machining (RUM) for preparing asymmetric cutting edge microgeometries of various shapes (chamfers, circular, and elliptical rounding and their combinations) on a CBN cutting tool. In this article, a new type of advanced cutting edge preparation method is presented. CBN is relatively resistant to the most often used (abrasive) methods of cutting-edge preparation, due to its very high hardness (which is a prerequisite property for machining difficult-to-cut materials). Such hard materials could be processed using advanced manufacturing methods, and rotary ultrasonic machining (RUM) is one such method. Experiments have shown that RUM can be used for machining CBN. However, high hardness is not the only challenge here. For cutting edge preparation, it is necessary to achieve an adequate accuracy of size and dimensions. The presented paper analyzes the suitability of the RUM process for processing CBN inserts. The results of the experiment showed that this method can be used for preparing asymmetric cutting edge microgeometries with various shapes.